A thousand splendid suns. - Hosseini, Khaled, ....- (London : Bloomsbury, 2008)
Mariam is only fifteen when she is sent to Kabul to marry Rasheed. Nearly two decades later, a friendship grows between Mariam and a local teenager, Laila, as strong as the ties between mother and daughter. When the Taliban take over, life becomes a desperate struggle against starvation, brutality and fear. Yet love can move a person to act in unexpected ways, and lead them to overcome the most daunting obstacles with a startling heroism.
Keywords: Fiction